Islamisasi Sains Syed Naquib Al-Attas dan Penolakan Bassam Tibi - Nurul Embun Isnawati; Urfun Nadhiroh; Khoirotun Nisa’ Privani; Rhegita Dewi Ramdhany; Ahmad Fauzan Hidayatullah (Universitas Muhammadiyah Magelang, 2020)
This study aims to elaborate on the differences in the views of the Islamization of science between Syed Naquib Al-Attas and Bassam Tibi. The study uses a literature review from relevant sources. Al-Attas's thought is based on his concern for the doctrine that scientific terminology is identical to western civilization. Al-Attas carried out the movement of modernization and Islamization, this is a concrete effort in the human's liberation from the shackles of secular understanding confined in magical and mythological traditions that are contrary to Islam. However, Bassam Tibi rejects this opinion. Bassam Tibi opposes the Islamization because it is a form of indigenization which is related to the cultural strategy of Islamic fundamentalism, integrally. Islamization is considered as a reaffirmation of local knowledge to face global knowledge and cultural invasion